2002
DOI: 10.2117/psysoc.2002.162
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Character-Component Interaction in Chinese Character Perception

Abstract: The PISA (parallel input serial access) model assumes independence and competition of word-level and letter-level processing (Allen & Madden, 1990;Allen & Emerson, 1991), while the IA (interactive activation) model proposes that wordlevel and letter-level processing interactively exchange information (McClelland & Rumelhart, 1981). This current study attempts to explore which of these two views characterizes the character-component relationship in Chinese character recognition using the component detection tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition to the dual-route account that assumes an active role for the reader in selectively setting a processing priority for the phonetic radical when the character frequency is low, the current findings can also be interpreted in terms of the results of a race between the character and the component channel of processing (Huang & Wang, 1992;Wang, 2002). The radical wins the race with the character channel only when the character frequency is low (Chen, 1986;Drewnowski & Healy, 1977;Wang, 2002). As such, the phonetic radical is activated more readily than the semantic radical probably because it is always internally represented (a stand-alone character) (Ding et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to the dual-route account that assumes an active role for the reader in selectively setting a processing priority for the phonetic radical when the character frequency is low, the current findings can also be interpreted in terms of the results of a race between the character and the component channel of processing (Huang & Wang, 1992;Wang, 2002). The radical wins the race with the character channel only when the character frequency is low (Chen, 1986;Drewnowski & Healy, 1977;Wang, 2002). As such, the phonetic radical is activated more readily than the semantic radical probably because it is always internally represented (a stand-alone character) (Ding et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
“…In this latter case, there would not be any effect of location. Character frequency and radical frequency are also manipulated in all experiments since past studies have demonstrated that they may interact with the activation of orthographic components in both English (Allen & Madden, 1990;Drewnowski & Healy, 1977;Healy & Drewnowski, 1983;Johnson, Allen, & Strand, 1989) and Chinese (Chen, 1986;Wang, 2002). Radical token frequency (i.e., radical frequency weighed by the frequency of the character in which the radical is present), rather than radical type frequency, is examined here because the former reflects the familiarity of the radical to the participant (Fang & Wu, 1989; and supposedly plays a role in the radical activation process (cf.…”
mentioning
confidence: 99%
“…Linguistic frequency Ding, Peng, & Taft, 2004;Hue, 1992Hue, , 2003Kuo et al, 2003;Lee et al, 2004;Lee et al, 2005;Liu et al, 2006;Lo, Hue, & Tsai, 2007;Seidenberg, 1985;Taft & Zhu, 1997;Wang, 2002Wang, , 2006 Character complexity Chen, Allport, & Marshall, 1996;Perfetti & Tan, 1998;Seidenberg, 1985;Taft & Zhu, 1997;Tan, Feng, Fox, & Gao, 2001;Wang, 2002Wang, , 2006Weekes, Chen, & Lin, 1998 Type of characters Fang, Horng, & Tzeng, 1986;Hue, 1992;Leck, Weekes, & Chen, 1995;Wang, 2002Wang, , 2006Weekes et al, 1998;Weekes & Zhang, 1999 Orthographic, semantic, and phonological relationship in pairs of characters Leck et al, 1995;Liu et al, 2006;Perfetti & Tan, 1998;Weekes et al, 1998 Position of radical or phonetic component in character Chen et al, 1996;Ding et al, 2004;Feldman & Siok, 1997;Hsiao, Shillcock, & Lee, 2007;Lo et al, 2007;Wang, 2002Wang, , 2006 Character regularity Hue, 1992;Lee et al, 2005;Seidenberg, 1985;…”
Section: Variable Studymentioning
confidence: 99%